Cisco bring your own device (BYOD) networking - Redmon, Kevin (LiveLessons., 2014)
"Cisco Bring Your Own Device (BYOD) Networking LiveLessons will introduce the viewer to the Cisco BYOD Smart Solution, focusing on version 2.5 of the Cisco Validated Design (CVD). The topics explained in this series will focus on the Cisco Smart Solution, but may be ubiquitous across other BYOD implementations. Cisco Bring Your Own Device (BYOD) Networking LiveLessons will begin with an explanation of the business model that makes BYOD such an appealing movement for IT organizations, from small businesses to large enterprises. As the business case is established, the author will then discuss the complete end-to-end BYOD architecture, taking a deep dive within each major topic area. The video training will cover everything from wired switchport access, wireless LAN configuration using Lightweight Access Points, as well as Guest access. The author will sometimes enrich the discussion points beyond the CVD topics to provide a complete, well-rounded approach to the Cisco BYOD Smart Solution."--Resource description page.